Tai Chi on bone mineral density of postmenopausal osteoporosis: A protocol for systematic review and meta-analysis. Issue 36 (4th September 2020) - Wu, Hai-Yang; Wang, Yi-Ru; Wen, Guo-Wei; Tang, Zhen-Yin; Yu, Yi-Qun; Zhang, Ji-Ren; Liu, Ping; Wu, Jun-Hao
Abstract: Background: Osteoporosis is a clinically common metabolic disease, especially in postmenopausal women. Tai Chi might be beneficial in osteoporosis patients. This study will be performed to examine the effects of Tai Chi on bone mineral density of postmenopausal osteoporosis. Methods: We will search the electronical databases and hand-searching journals or reference lists. The study screening and data extraction will be carried out by 2 investigators independently. The primary outcome is bone mineral density (lumbar spine, Ward's triangle, trochanter, proximal femur, femoral neck, or total hip). Secondary outcomes are pain score, alkaline phosphatase, osteocalcin, and adverse effects. Review Manager V.5.3 software will be used to compute the data. Results: The results of the study will provide a reliable evidence to assess the effects of Tai Chi on bone mineral density of postmenopausal osteoporosis. Conclusion: The conclusion of our systematic review will answer whether Tai Chi is an effective intervention to improve bone mineral density of postmenopausal osteoporosis.